(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2021)
Cathepsin B, an abundant expressed cysteine peptidase, plays a key role in cancer cell proliferation, tumor metastasis, apoptosis, angiogenesis, invasion and migration. Therefore, development of cathepsin B inhibitors to treat cancer is of great significance. In this study, dihydronaphthalenone chalconoid derivatives containing different benzyliden moieties were synthesized via an efficient route in microwave condition that resulted in the desired compounds in high yields compared to acid- or base-catalyzed refluxing conditions. Cytotoxicity of the compounds was evaluated against K562, HT-29 and MCF-7 human cancer cell lines by MTT assay. P1, P3 and P9 (containing 4-OCH3, 3-NO2 and 4-CN moieties on phenyl ring, respectively) exhibited good cytotoxic activity with an IC50 range of 7.1-28.9 μM. Molecular docking analysis was carried out to investigate the possible interactions and binding modes of all compounds with cathepsin B. The most promising compounds, P1, P3 and P9 were well accommodated within the active site and had the least estimated free binding energies. It was concluded from both MTT assay and docking studies that some dihydronaphthalenone chalconoid derivatives could be suggested as effective cytotoxic agents and potential cathepsin B inhibitors.